Cost-effectiveness of immunization strategies to protect infants against respiratory syncytial virus in the Netherlands - Annefleur C. Langedijk; Floris van den Dungen; Lisette Harteveld; Jennie van den Boer; Lucy Smit; Ahuva Averin; Erin Quinn; Mark Atwood; Amy Law; Diana Mendes; Marlies van Houten (Human Vaccines & Immunotherapeutics, 2025)
The European Medicines Agency has authorized two interventions to prevent lower respiratory tract disease due to respiratory syncytial virus (RSV-LRTD) in infants: nirsevimab, a monoclonal antibody, and bivalent stabilized prefusion F subunit maternal vaccine (RSVpreF). In the Netherlands, RSV-LRTD protection is recommended for all infants with nirsevimab given preferential recommendation over RSVpreF. We evaluated cost-effectiveness of various intervention strategies to prevent RSV in the Netherlands. We employed a cohort model to evaluate clinical and economic outcomes associated with RSV-LRTD during the first year of life among infants receiving RSVpreF with complementary nirsevimab and, alternatively, nirsevimab alone versus no intervention. Model inputs, based principally on Dutch data, include rates of disease, case-fatality, general mortality; disutility; and costs of interventions, medical care, treatment-related travel, and disease-associated work loss. Uptake of interventions assumed 70%; effectiveness was based on a published study using Phase III trial data. Analyses were conducted from the societal perspective using 2023 EUR; annual discount rates were 3% for costs and 1.5% for quality-adjusted life-years (QALYs). With no intervention, there were 10,482 RSV-LRTD cases with total associated costs of € 17.4M. Nirsevimab alone prevented 4,905 cases, yielding 100 QALYs; total costs increased by € 59.3M due to high intervention costs and cost-effectiveness was € 592,404/QALY (vs. no intervention). RSVpreF with complementary nirsevimab for infants prevented 4,723 cases, yielding 108 QALYs; total costs increased by € 35.5M and cost-effectiveness was € 329,187/QALY (vs. no intervention). Maternal RSVpreF with complementary nirsevimab was more cost-effective than nirsevimab alone.